The Guiding Role of Home Economics In Improving Nutrition and Healthcare Patterns for Rural Women In Southern Libya - Mabrouka Ali Al-Mabrouk; Dr. Ikhlas Obaid Saeed Al-Subaie (Journal of Scientific and Human Dimensions, 2026)
This study aims to analyze the guiding role of home economics in improving dietary patterns and healthcare practices among rural women in southern Libya by enhancing health awareness, promoting healthy nutritional behaviors, and supporting community engagement. The study adopts a descriptive-analytical approach through the review and analysis of relevant local and international reports and documents. The findings indicate that rural women face multiple health challenges, including weak healthcare infrastructure, a shortage of qualified medical personnel, and low levels of health awareness. The results show that 45% of women have a moderate level of health awareness, compared to 30% with a high level and 25% with a low level, highlighting the need to strengthen health education programs. Regarding dietary practices, 60% of women rely on fruits and vegetables, while 25% consume saturated fats, indicating both positive patterns and areas requiring improvement. Additionally, 60% of women participate in home-based agriculture, contributing to household food security. The study further highlights that home economics represents a practical, cost-effective approach to strengthening preventive health and achieving food security through efficient household resource management. It concludes that empowering rural women both cognitively and economically significantly improves family health outcomes. The study recommends strengthening health education programs, expanding primary healthcare services, and integrating home economics into development policies to support sustainable development goals.